1997
DOI: 10.2166/wst.1997.0575
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis in sediments from deep lakes at different temperatures (2–70°C)

Abstract: Methanogenic degradation of organic matter occurs in a wide temperature range from psychrophilic to extreme thermophilic conditions. Mesophilic and thermophilic methanogenesis is relatively well investigated, but little is known about low temperature methanogenesis and psychrophilic methanogenic communities. The aim of the present work was to study methanogenesis in a wide range of temperatures with samples from sediments of deep lakes. These sediments may be considered deposits of different types of microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 0 publications
7
64
2
Order By: Relevance
“…Along with the reactivity of the organic matter, temperature is an important regulator of organic matter degradation in sediments (Gudasz et al, 2010;Kelly and Chynoweth, 1981;Nozhevnikova et al, 1997), and consequently also of CH 4 production (Bastviken, 2009). However, at the shorter timescales of the present study, variations in temperature are small and hence the effect on methanogenesis is most likely also smaller.…”
Section: Temperature Versus Lake Level Responsementioning
confidence: 70%
“…Along with the reactivity of the organic matter, temperature is an important regulator of organic matter degradation in sediments (Gudasz et al, 2010;Kelly and Chynoweth, 1981;Nozhevnikova et al, 1997), and consequently also of CH 4 production (Bastviken, 2009). However, at the shorter timescales of the present study, variations in temperature are small and hence the effect on methanogenesis is most likely also smaller.…”
Section: Temperature Versus Lake Level Responsementioning
confidence: 70%
“…Previous studies, however, have often reported that acetate fermentation is the major pathway of methanogenesis in profundal lake sediments (Schulz and Conrad, 1996;Schulz et al, 1997;Nozhevnikova et al, 1997). This inconsistency with previous studies might be explained by indirect methane production from CO 2 via autotrophic acetogenesis (Nozhevnikova et al, 1997;Hornibrook et al, 2000). Carbon isotope fractionation for acetate production from H 2 and CO 2 was reported to be compatible with that for the methanogenesis of the CO 2 reduction pathway (Gelwicks et al, 1989).…”
Section: Fig 3 Methane Content Vs (A) Water Depth (B) ∑Co 2 (C)mentioning
confidence: 71%
“…Two primary metabolic pathways are generally recognized for biological methanogenesis: fermentation of acetate and reduction of carbon dioxide, and the low δ 13 C CH 4 values and high αcCO 2 -CH 4 values both suggested that methane in the sediments of Lake Biwa is predominantly produced via CO 2 reduction pathway (Whiticar et al, 1986;Sugimoto and Wada, 1993). Previous studies, however, have often reported that acetate fermentation is the major pathway of methanogenesis in profundal lake sediments (Schulz and Conrad, 1996;Schulz et al, 1997;Nozhevnikova et al, 1997). This inconsistency with previous studies might be explained by indirect methane production from CO 2 via autotrophic acetogenesis (Nozhevnikova et al, 1997;Hornibrook et al, 2000).…”
Section: Fig 3 Methane Content Vs (A) Water Depth (B) ∑Co 2 (C)mentioning
confidence: 99%
“…At low temperatures, hydrogenotrophic methane production is thought to be inhibited, shifting methanogenesis toward acetate or C1 compounds (Zeikus and Winfrey, 1976;Gunnarsson and Ronnow, 1982;Schulz and Conrad, 1996;Nozhevnikova et al, 1997). Despite this limitation, a few species of Methanogenium have been observed and even isolated from psychrophilic sulfate-rich marine sediments (Parkes et al, 1990;Franzmann and Liu, 1997;Chong et al, 2002;Purdy et al, 2003;Kendall and Boone, 2006).…”
Section: Discussionmentioning
confidence: 99%